Technology for obtaining porous high-purity anatase phase titanium dioxide film on surface of flexible matrix material - YIN XU; YANG JIJUN; LIU BO; WANG YUAN (2011)
The invention discloses a technology for obtaining a porous high-purity anatase phase titanium dioxide film on a surface of a polyimide flexible matrix material. The technology comprises the following steps: rinsing a flexible matrix, washing by ion bombardment, depositing a metal chromium transition layer and a metal titanium nano film by a direct current/radio frequency magnetron sputtering method, obtaining the porous high-purity anatase phase titanium dioxide film with preferred orientation by plasma microarc oxidation in situ, etc. The technology of the invention breaks through the difficulty in the traditional film preparation method that the porous high-purity anatase phase titanium dioxide film with excellent bonding property is difficult to be obtained on the polyimide flexible matrix surface which is easy to deform and is not resistant to high temperature; and the technology is easy to realize mass production and industrial popularization. The technology of the invention also overcomes the problems